2019
DOI: 10.1038/s41598-019-44174-7
|View full text |Cite
|
Sign up to set email alerts
|

Time course images of cellular injury and recovery in murine brain with high-resolution GRIN lens system

Abstract: Time course, in vivo imaging of brain cells is crucial to fully understand the progression of secondary cellular damage and recovery in murine models of injury. We have combined high-resolution gradient index lens technology with a model of diffuse axonal injury in rodents to enable repeated visualization of fine features of individual cells in three-dimensional space over several weeks. For example, we recorded changes in morphology in the same axons in the external capsule numerous tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
(94 reference statements)
3
17
0
Order By: Relevance
“…In the same study, we further visualized their rapid induction in an mTBI mouse model, where the usage of Thy1-YFP transgenic mice was the key to clearly visualize such axonal change (Gu et al, 2017 ). Importantly, consistent with our results, there are several recent studies showing rather rapid induction of axonal varicosities in vivo in different types of mTBI mouse models (Marion et al, 2018 ; Vascak et al, 2018 ; Ziogas and Koliatsos, 2018 ; Pernici et al, 2019 ; Weber et al, 2019 ). Therefore, rapid and reversible formation of axonal varicosities in CNS neuron mechanosensation is likely a new form of neural plasticity that is related to mechanical injury.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the same study, we further visualized their rapid induction in an mTBI mouse model, where the usage of Thy1-YFP transgenic mice was the key to clearly visualize such axonal change (Gu et al, 2017 ). Importantly, consistent with our results, there are several recent studies showing rather rapid induction of axonal varicosities in vivo in different types of mTBI mouse models (Marion et al, 2018 ; Vascak et al, 2018 ; Ziogas and Koliatsos, 2018 ; Pernici et al, 2019 ; Weber et al, 2019 ). Therefore, rapid and reversible formation of axonal varicosities in CNS neuron mechanosensation is likely a new form of neural plasticity that is related to mechanical injury.…”
Section: Introductionsupporting
confidence: 93%
“…Collectively, this experimental result confirmed that axonal varicosities indeed rapidly form upon mechanical impact in vivo in the mouse model of repetitive mTBI, suggesting that at least some axonal varicosities were induced by the primary injury in mTBI. Since 2018, several groups independently reported that axonal varicosities were induced from a few hours to 2 days after impact in the brain of different mTBI mouse models (Marion et al, 2018;Ziogas and Koliatsos, 2018;Pernici et al, 2019;Weber et al, 2019), consistent with the findings using rcTBI.…”
Section: Axonal Varicosities Induced By Mechanical Impact In Vivosupporting
confidence: 70%
See 1 more Smart Citation
“…Images were scanned in three dimensions with x- and y-dimensions of 248 Ī¼m (1024 Ɨ 1024-pixel resolution), with z-steps of 2 Ī¼m (z stack) to produce z stacks of 36 and 46 Ī¼m to ensure that all cells were captured within the volume. Pixel dwell time was set to 2 Ī¼L with pixel averaging of 5/scan to acquire z stack images [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of experimental studies using a number of different controlled brain injuries in rodents focused on the very early period after TBI, in particular the cellular, inflammatory and molecular mechanisms that orchestrate beneficial shielding of non-injured tissue and repair, but also pro-inflammatory secondary damage [35][36][37] . In contrast to the substantial advance in the understanding of early post-TBI events, long-lasting, protracted changes of behavior are less well studied.…”
mentioning
confidence: 99%